Genesis : a commentary - von Rad, Gerhard, 1901-1971; Marks, John H. (London, UK : SCM, 1972)
Includes bibliographical references.
1st published in English, 1961. 2nd English edition published 1963. Originally published in German: Das erste Buch Mose, Genesis (Das Alte Testament Deutch 2-4).-- Gottingen : Vanenhoeck and Ruprecht, 1949.
Keywords: Bible. -- commentaries